2008
DOI: 10.1021/ef800143h
|View full text |Cite
|
Sign up to set email alerts
|

Effect of the Coal Particle Size on Pyrolysis and Char Reactivity for Two Types of Coal and Demineralized Coal

Abstract: A better understanding of the influence of particle size on pyrolysis and char reactivity is of crucial importance in optimizing the integrated process combining coal topping (coal fast pyrolysis) with char gasification. Different size fractions of two types of coal and demineralized coal were pyrolyzed in a spouted bed. The resulting chars were characterized by X-ray diffraction, and char reactivity was determined in a thermogravimetric analyzer (TGA). Within the range of particle sizes investigated, an incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
35
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 18 publications
0
35
0
Order By: Relevance
“…Transport limitations during heating are reduced for smaller particles, resulting in a higher effective heating rate. Although research in this area has been limited, initial particle size has been observed to have an impact on morphology of biomass chars (Avila et al, 2011) and on reactivity of coal chars (Zhu et al, 2008). Experimental particle size distributions in the present study (given below) reflect the anticipated differences between torrefied and raw biomass that will occur in full-scale devices.…”
Section: Introductionmentioning
confidence: 75%
“…Transport limitations during heating are reduced for smaller particles, resulting in a higher effective heating rate. Although research in this area has been limited, initial particle size has been observed to have an impact on morphology of biomass chars (Avila et al, 2011) and on reactivity of coal chars (Zhu et al, 2008). Experimental particle size distributions in the present study (given below) reflect the anticipated differences between torrefied and raw biomass that will occur in full-scale devices.…”
Section: Introductionmentioning
confidence: 75%
“…Different products are generated in the different steps of pyrolysis. The weight loss behavior and product composition of pyrolysis are affected by many factors, including temperature, heating rate, particle size, mineral, coal type and petrography (Ghetti, 1986;Özbas, 2003;Kizgut and Yilmaz, 2003;Zhu et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…The positive effect of torrefaction on energy consumption during biomass size reduction can be captured only if the large particle size of biomass is utilized in the torrefaction process. A large particle size induces higher char production and lower liquid yield in the pyrolysis process [5][6][7]. However, how this affects the torrefaction process, or product yield and quality is not known.…”
mentioning
confidence: 99%